APPLICATION OF BUDESONIDE IN BREASTFEEDING MOTHERS WITH BRONCHIAL ASTHMA - E.A. Vishneva; L.S. Namazova-Baranova (Педиатрическая фармакология, 2009)
Bronchial asthma is a chronic inflammatory disease of respiratory tract. Breastfeeding mothers suffering from bronchial asthma require attention and control over their health status. The results of research described in the article confirm the need for a continued baseline therapy using the inhalant budesonide in the breastfeeding period and allow mothers suffering from bronchial asthma to be sure of safety in application of modern optimal anti-inflammatory disease treatment and not to worry about a possibility of systemic effect of the medication on the baby.Key words: budesonide, inhalant glucocorticosteroids, breast milk.